REKONSTRUKSI DASAR-DASAR PEMIKIRAN PENDIDIKAN IPS-SD BERDASARKAN PERSPEKTIF KONSTRUKTIVISME - Farisi, Mohammad Imam (2005)
he aims of this research are to find out and to reconstruct: (1) the basic competencies of elementary social studies which the elementary students should have; (2) the pattern and structure of elementary social studies curriculum content organization, which will be able to give meaningful learning experiences for the students; and (3) the pattern of conducive classroom atmosphere arrangement which able students to have basic competencies (personal, social, and intellectual); which can be used by the students to develop their ability to build their own structure of knowledge, values, attitudes, and actions in their personal and socio-cultural life. The research was conducted in the National Elementary School Lawangan Daya II, district of Pademawu, Pamekasan Municiple. Research subjects are teacher of elementary social studies and students of grade IV and V. Data were collected through in-depth interview; observation participation in and outside class; and content analysis of documents. They were processed and analyzed by using qualitative approach. The findings of this research are: (1) the basic competencies of elementary social studies which the elementary students should have are: personal competencies which cover: self-concept and self-understanding, objective attitudes toward themselves, self-actualization, self-creativity, and carry out to religious values and attitudes; social competencies which cover: self-understanding and self-awareness toward themselves as members of society; to morality and ethic, and to gender, ethnic, and cultural equality and diversity; communication skills, social interaction, social participation, and work together with others; pro-social or altruism attitudes; intellectual competencies which cover: critical, reflective, contextual, and pragmatic thinking; spatial/geographical and mathematic-logic skills; understanding and awareness about time, historical understanding and mindedness; (2) the content of elementary social studies curriculum is organized as learning experiences giving pedagogical, socio-cultural, and psychological meanings for the student, based on principle of "a reconstruction of student's psychological, socio-cultural, and intellectual horizons"; having contextual in character, and circular, spiral, sequential in pattern. The structures of curriculum content of elementary social studies are: substantive structure, syntactic structure, and normative structure, which are eclectically based on students' experiences, socio-cultural context, and scientific knowledge; (3) the pattern of classroom atmosphere arrangement is developed as psychological and socio-cultural context for students to dialogue, interact, and negotiate their subjective and inter-subjective meanings, by mediating and facilitating teacher, learning activities, and by maximizing the use of learning materials and media. The recommendations of this study are: to all experts, researchers, program and text-book developers, study program of social studies in post graduate, and practitioners of elementary social studies to analyze, develop, and implement of the findings and reconstructions of this study in arranging the basic competencies, pattern and structure of curriculum content organization, and pattern of classroom atmosphere of elementary social studies.